Phosphine-substituted 1, 2, 3-triazoles as P, C- and P, N-ligands for photoluminescent coinage metal complexes. Issue 41 (14th May 2019) - Seifert, Tim P.; Bestgen, Sebastian; Feuerstein, Thomas J.; Lebedkin, Sergei; Krämer, Felix; Fengler, Christian; Gamer, Michael T.; Kappes, Manfred M.; Roesky, Peter W.
Abstract : A series of homo- and hetero-polynuclear coinage metal complexes based on a phosphine-substituted 1, 2, 3-triazole system was synthesized. Abstract : A series of homo- and hetero-polynuclear coinage metal complexes based on a phosphine-substituted 1, 2, 3-triazole system is presented. Besides the P, N-ligand 1-benzyl-4-(diphenylphosphanyl)-1 H -1, 2, 3-triazole (L PN ), the P, C-donor ligand 1-benzyl-4-(diphenylphosphanyl)-3-methyl-1 H -1, 2, 3-triazolium (L PC H + ), featuring a potential mesoionic carbene moiety, was obtained by methylation of L PN . Starting from the monogold chloride complexes AuCl(L PN /L PC ), the syntheses of a heterotrinuclear Au2 Cu complex as well as a digold carbene complex are described. The multinuclear complexes show metallophilic interactions. Their photophysical properties were investigated by temperature-dependent photoluminescence (PL) measurements. In particular, the digold complex shows interesting PL properties including narrow exciton peaks arising in the excitation and emission spectra below 50 K. These might be related to the molecular 'chains' in the crystal structure of the digold complex, formed by phenyl ligand stacking.